Statistics using SPSS : an integrative approach. - Lawner Weinberg, Sharon, ....-; Knapp Abramowitz, Sarah, ....- (Cambridge : Cambridge University, 2008)
This is an introductory applied statistics text that can be used for a one- or two-semester course at either the undergraduate or graduate level. Central features are its hands-on approach; the use of real data; the wealth of exercises and illustrated examples using these data; the complete set of detailed answers to exercises in an appendix; the presentation of statistical methods with a clear, conceptual emphasis that includes an historical account of each method; and the integration of SPSS in a way that reflects statistical practice. Step-by-step instructions for using SPSS are provided as each new analytic procedure is introduced. A data CD is included with the text so that students may conduct their own statistical analyses and learn firsthand how statistics is used in practice.